2020
DOI: 10.1177/0038026120963367
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Australia’s baby boomers and intergenerational equity

Abstract: Australia’s Intergenerational Reports (2010, 2015) make a case for restraining public expenditure on an ageing population given the sizeable post-WWII baby boom cohort, increasing longevity, and uncertain economic prospects for younger generations. There also is concern for major disparities within older and younger generations resulting from cumulative advantages or disadvantages over the life course. Drawing on national survey data from the Attitudes to Ageing in Australia study, this article investigates pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
2
1
1
Order By: Relevance
“…A high negative impact of these three lifestyle risk factors was also reported on HLE between mid to early older age (age 50–75) participants in a multi-cohort study across four European countries (UK, Sweden, France and Finland), suggesting that women with at least two of the unhealthy lifestyle risk factors had on average 7 years lower HLE than those with no risk factors [ 31 ]. Our findings do not provide evidence that the 1946–51 cohort (first cohort baby boomers generation) are ageing in better health than previous generations [ 45 ] and emphasise that such gains are dependent on educational status and health behaviours. However, it is important to note that women in the older generation (1921–26) are likely to be a healthier group of 70 year old people (i.e., healthier survivors) than the younger generation (1946–51) when they get to 70.…”
Section: Discussioncontrasting
confidence: 74%
“…A high negative impact of these three lifestyle risk factors was also reported on HLE between mid to early older age (age 50–75) participants in a multi-cohort study across four European countries (UK, Sweden, France and Finland), suggesting that women with at least two of the unhealthy lifestyle risk factors had on average 7 years lower HLE than those with no risk factors [ 31 ]. Our findings do not provide evidence that the 1946–51 cohort (first cohort baby boomers generation) are ageing in better health than previous generations [ 45 ] and emphasise that such gains are dependent on educational status and health behaviours. However, it is important to note that women in the older generation (1921–26) are likely to be a healthier group of 70 year old people (i.e., healthier survivors) than the younger generation (1946–51) when they get to 70.…”
Section: Discussioncontrasting
confidence: 74%
“…For example, the SCM stereotype of the elderly as warm but incompetent is expected to elicit pity and to foster active support (e.g., Cuddy et al, 2005). This is generally consistent with the welfare policy context in which the government‐provided Age Pension has not been a target of major welfare reform, and the public continue to support widespread eligibility (O’Loughlin et al, 2021). In contrast, the negative stereotype of unemployed income support recipients suggests they will elicit feelings of contempt.…”
Section: Discussionsupporting
confidence: 72%
“…Rather than acknowledging the changing social and economic lives of young people, the Boomer group emphasised a diminishing culture of hard work and delayed gratification as central drivers for declining home ownership among young people. This finding is consistent with Australian research by O'Loughlin et al (2021), which found that across two time points -2009/2010, 2015-2017 -older cohorts, and particularly baby boomers, were likely to believe that they received less than their fair share of government benefits (O'Loughlin et al, 2021).…”
Section: The Sociological Review 69(4)supporting
confidence: 90%
“…This is despite some evidence of real reductions in the prospects of younger cohorts in key areas, such as employment transitions and housing, relative to previous cohorts. While some older Australians face financial peril, with class and gender differences remaining substantial, the baby boomer cohort has on average benefited through policy shifts in taxation and housing policy that have favoured their cohort (O'Loughlin et al, 2021).…”
Section: Technological Anxiety Globalisation and Ethical Awarenessmentioning
confidence: 99%